2023
DOI: 10.1101/2023.03.08.531834
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Further evidences of an emerging stingless bee-yeast symbiosis

Abstract: Symbiotic interactions between microorganisms and social insects have been described as crucial for the maintenance of these multitrophic systems, as observed for the stingless beeScaptotrigona depilisand the yeastZygosaccharomycessp. The larvae ofS. depilisingest fungal filaments ofZygosaccharomycessp. to obtain ergosterol, which is the precursor for the biosynthesis of ecdysteroids that modulate insect metamorphosis. In this work we verified that nutritional fungal symbioses also occur in other species of st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…and Monascus ruber ) in the larval cell, maintaining Zygosaccharomyces at a level beneficial to the developing larvae (Paludo et al 2019 ). Similar filamentous growth forms of Zygosaccharomyces species have been isolated from brood cells of eight additional stingless bee species ( Scaptotrigona bipuctata, S. postica, S. tubiba, Tetragona clavipes, Melipona quadrifasciata, M. fasciculata, M. bicolor , and Partamona helleri ), suggesting similar nutritional roles in larval development (de Paula et al 2023 ). Additionally, larvae of the stingless bee species Heterotrigona itama , native to Malaysia, also show increased mortality (37% survival) when reared on sterile diet compared to natural diet (85%) or diet supplemented with the fungus Panus lecomtei isolated from provisions (57%, Razali et al 2022 ).…”
Section: Functions Of Bee-associated Fungimentioning
confidence: 65%
“…and Monascus ruber ) in the larval cell, maintaining Zygosaccharomyces at a level beneficial to the developing larvae (Paludo et al 2019 ). Similar filamentous growth forms of Zygosaccharomyces species have been isolated from brood cells of eight additional stingless bee species ( Scaptotrigona bipuctata, S. postica, S. tubiba, Tetragona clavipes, Melipona quadrifasciata, M. fasciculata, M. bicolor , and Partamona helleri ), suggesting similar nutritional roles in larval development (de Paula et al 2023 ). Additionally, larvae of the stingless bee species Heterotrigona itama , native to Malaysia, also show increased mortality (37% survival) when reared on sterile diet compared to natural diet (85%) or diet supplemented with the fungus Panus lecomtei isolated from provisions (57%, Razali et al 2022 ).…”
Section: Functions Of Bee-associated Fungimentioning
confidence: 65%
“…Studies regarding ecological relationships and fungal species composition in substrates related to native bees are still rare. In Brazil, the relationship between fungi and Scaptotrigona depilis has been investigated [28][29][30]. In addition, other studies have reported the presence of different microorganisms associated with other genera of stingless bees [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…postica, Sc. tubiba, Tetragona clavipes, Melipona quadrifasciata, M. fasciculata, M. bicolor, and Partamona helleri (de Paula et al, 2023). Additionally, Liu et al (2023) have found an association between the gut microbiome composition and the flight traits of stingless bees, though not a causative one.…”
Section: Introductionmentioning
confidence: 99%
“…Fall armyworm (Spodoptera frugiperda) harbors fungal symbionts such as Fusarium oxysporum and Cladosporium sp (Watson et al, 2023). Like other insects, bees depend on a symbiotic relationship with microbes, ranging from pathogenic to mutually beneficial (de Paula et al, 2023;Rutkowski et al, 2023). Common fungal symbionts include yeasts from the taxa of Starmerella, Metschnikowia, Zygosaccharomyces, and Candida, which are found across various tribes and species (Rutkowski et al, 2023).…”
Section: Introductionmentioning
confidence: 99%